Sleep-Related Factors and Work-Related Injuries among Farmers in Heilongjiang Province, People’s Republic of China - Zhu, Huiping (MDPI, 2014)
The association between sleep and work-related injuries among Chinese farmers has not been well studied. This study examined the impact of lack of sleep on agricultural work-related injuries among farmers in China. Data were from a cross-sectional survey of farm-workers in northeastern China. Information was obtained on injuries that occurred in 12 months prior to the survey, on eight sleep-related variables, and on socio-demographic variables. Logistic regression analyses were conducted to test the hypothesis that lack of sleep significantly increased the risk of work-related injuries after controlling for other injury-related risk- factors. Farmers who slept less than six hours per night were 59% more likely to be injured than those who slept more than eight hours per night (OR = 1.59; 95% CI = 1.04, 2.41). The odds of a work-related injury was 2.46 (1.56–3.89) for farmers who reported going to sleep after midnight at least once a week compared with farmers who reported going to sleep after midnight once a month. Farmers who reported having difficulty falling asleep or waking frequently during the night, who often having nightmares, or who experienced daytime sleepiness were at higher injury risk compared with the reference group after controlling for age, gender and alcohol consumption. Reduced sleep hours and poor sleep quality significantly increased the risk of work-related injuries in Chinese farmers. Sleep hours and sleep quality should be considered when assessing occupational safety among farmers.